Genomic typing, antimicrobial resistance gene, virulence factor and plasmid replicon database for the important pathogenic bacteria Klebsiella pneumoniae - Andrey Shelenkov; Anna Slavokhotova; Yulia Mikhaylova; Vasiliy Akimkin (BMC Microbiology)
Abstract Background The infections of bacterial origin represent a significant problem to the public healthcare worldwide both in clinical and community settings. Recent decade was marked by limiting treatment options for bacterial infections due to growing antimicrobial resistance (AMR) acquired and transferred by various bacterial species, especially the ones causing healthcare-associated infections, which has become a dangerous issue noticed by the World Health Organization. Numerous reports shown that the spread of AMR is often driven by several species-specific lineages usually called the ‘global clones of high risk’. Thus, it is essential to track the isolates belonging to such clones and investigate the mechanisms of their pathogenicity and AMR acquisition. Currently, the whole genome-based analysis is more and more often used for these purposes, including the epidemiological surveillance and analysis of mobile elements involved in resistance transfer. However, in spite of the exponential growth of available bacterial genomes, their representation usually lack uniformity and availability of supporting metadata, which creates a bottleneck for such investigations. Description In this database, we provide the results of a thorough genomic analysis of 61,857 genomes of a highly dangerous bacterial pathogen Klebsiella pneumoniae. Important isolate typing information including multilocus sequence typing (MLST) types (STs), assignment of the isolates to known global clones, capsular (KL) and lipooligosaccharide (O) types, the presence of CRISPR-Cas systems, and cgMLST profiles are given, and the information regarding the presence of AMR, virulence genes and plasmid replicons within the genomes is provided. Conclusion This database is freely available under CC BY-NC-SA at https://doi.org/10.5281/zenodo.11069018 . The database will facilitate selection of the proper reference isolate sets for any types of genome-based investigations. It will be helpful for investigations in the field of K. pneumoniae genomic epidemiology, as well as antimicrobial resistance analysis and the development of prevention measures against this important pathogen.